Increasing atmospheric CO2 modifies durum wheat grain quality and pasta cooking quality. (May 2016) - Fares, Clara; Menga, Valeria; Badeck, Franz; Rizza, Fulvia; Miglietta, Franco; Zaldei, Alessandro; Codianni, Pasquale; Iannucci, Anna; Cattivelli, Luigi
Abstract: The present study focused on the quality traits of durum wheat grains (protein and content, gluten content, yellow pigment content), semolina (gluten index and yellow index) and pasta (firmness, yellow index, cooking time) obtained from 12 durum wheat genotypes grown under elevated atmospheric CO2 concentration in an open field Free Air CO2 Enrichment (FACE) experiment. The aims were to evaluate the impact of elevated CO2 on durum wheat pasta making related traits as well as investigate genetic differences existing in a panel of old and modern cultivars. The protein content showed a not significant decrease (7%), the GC decreased significantly (13.3%), while the GI showed an increasing significant tendency (14%). The overall pasta quality (firmness and weight) worsened in ELE. Correlation between all traits and pasta firmness demonstrated that the decrease in pasta firmness under ELE was correlated with GPC and GC while it was not with the GI. All varieties, although to different extent, showed lower pasta firmness values compared to the ambient condition. Among the varieties tested, some were more sensitive than others to the increased atmospheric CO2 concentration, a finding that can be exploited by breeding for designing novel genotypes with lower sensitivity to increased atmospheric CO2 . Highlights: 12 durum wheat genotypes under ELE in a FACE experiment were evaluated. Under ELE, gluten content decreased significantly while protein content unchanged. The gluten index showed an increasing tendency under elevated CO2 conditions of about 14%. The overall pasta quality (firmness and weight) worsened in ELE. The genotypes variability helps designing novel varieties with lower sensitivity to ELE.